Time to follow guidelines, protocols, and structured procedures in medical care and time to leap out - Kobo-Greenhut A; Notea A; Ruach M; Onn E; Hasin Y (Dove Medical Press, 2014)
Ayala Kobo-Greenhut,1–3 Amos Notea,2,3 Meir Ruach,4 Erez Onn,4 Yehunatan Hasin1 1Bar-Ilan University, Tel Aviv, Israel; 2Technion, Haifa, Israel; 3Kinneret College, Galilee, Israel; 4Baruch Padeh Medical Center, Poriya, Israel Abstract: Present medical practice encourages management according to written guidelines, protocols, and structured procedures (GPPs). Daily medical practice includes instances in which “leaping: from one patient management routine to another is a must. We define “frozen patient management:, when patient management leaping was required but was not performed. Frozen patient management may cause significant damage to patient safety and health and the treatment quality. This paper discusses the advantages and disadvantages of GPP-guided medical practice and gives an explanation of the problem of frozen patient management in light of quality engineering, control engineering, and learning processes. Our analysis of frozen patient management is based on consideration of medical care as a process. By considering medical care processes as a closed-loop control process, it is possible to explain why, when an indication for deviation from the expected occurs, it does not necessarily attract the medical teams' attention, thereby preventing the realization that leaping to an alternative patient management is needed. We suggest that working according to GPPs intensifies the frozen patient management problem since working according to GPPs relates to “exploitation learning behavior”, while leaping to new patient management relates to “exploration learning behavior”. We indicate practice routines to be incorporated into GPP-guided medical care, to reduce frozen patient management. Keywords: guidelines, protocols, structured procedures, frozen patient management, close loop